2008
DOI: 10.1016/j.neuroimage.2008.03.030
|View full text |Cite
|
Sign up to set email alerts
|

T1ρ MRI of Alzheimer's disease

Abstract: Alzheimer's disease (AD) is the most common form of dementia in the elderly. Classic symptoms of the disease include memory loss and confusion associated with the hallmark neuro-pathologic lesions of neurofibrillary tangles (NFT) and senile plaques (SP) and their sequelae, gray matter atrophy. Volumetric assessment methods measure tissue atrophy, which typically follows early biochemical changes. An alternate MRI contrast mechanism to visualize the early pathological changes is T 1ρ (or "T-1-rho"), the spin la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
85
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 35 publications
6
85
2
Order By: Relevance
“…The loss of proteoglycan in cartilage is a characteristic event in the early stages of osteoarthritis, and the T 1ρ relaxation has the potential to follow this process [1][2][3][4][5]. Besides this, T 1ρ imaging is also found useful in a number of other applications [6][7][8][9][10][11][12]. In T 1ρ imaging, the spins are tipped into the transverse plane in one axis.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of proteoglycan in cartilage is a characteristic event in the early stages of osteoarthritis, and the T 1ρ relaxation has the potential to follow this process [1][2][3][4][5]. Besides this, T 1ρ imaging is also found useful in a number of other applications [6][7][8][9][10][11][12]. In T 1ρ imaging, the spins are tipped into the transverse plane in one axis.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that an alternate MRI contrast mechanism, T 1 ρ (T1rho), which is the spin lattice relaxation time constant in the rotating frame, can distinguish between AD and age-matched controls [5, 10]. In biological tissues, T 1 ρ relaxation may have contributions from several interactions.…”
Section: Introductionmentioning
confidence: 99%
“…T1ρ has been studied to a limited extent in several neuroimaging applications including the evaluation of ischemia [11,23,24], neurodegenerative disorders [17,18], demyelinating disease [20,21], animal models of brain tumor [1214,25], and response to gene therapy [15,16]. Although the exact mechanisms governing T1ρ relaxation are not fully understood, several factors proposed to influence T1ρ include scalar coupling, dipole–dipole interactions, and chemical exchange processes [26].…”
Section: Discussionmentioning
confidence: 99%
“…T1ρ can be used to probe macromolecular interactions and has been shown to reflect normal aging as well as pathologic changes in tissue protein and pH content [911]. A small number of published reports have shown potential applications of T1ρ neuroimaging to evaluate tumor boundaries [1216], neurodegenerative disease [1719], demyelination [20,21], psychiatric disease [22], and acute cerebral ischemia [11,23,24]. …”
Section: Introductionmentioning
confidence: 99%